Improvement of interfacial adhesion of unidirectional textile grade carbon fiber (TCF) with unsized, epoxy and urethane sizing reinforced in thermoset urethane composites. (September 2021) - Kore, Surbhi; Theodore, Merlin; Pillai, Renjith; Thomas, Vinoy; Vaidya, Uday
Abstract: This work considers a unique wide tow (450k filaments) form of low-cost carbon fiber intended for non-aerospace applications. TCF is currently produced in epoxy and urethane sizing, and there is a need to understand its resulting composite properties. In this study, the interfacial adhesion of sized TCF reinforced in thermoset urethane (TSU) composites are examined through the surface, thermal and mechanical characterization techniques. Atomic force microscopy (AFM) results showed an increase in surface roughness for urethane (276%) and epoxy sized (78%) versus unsized TCF. XPS results showed 531% increase in O in epoxy sized TCF and 250% N content in urethane sized TCF compared to unsized TCF. The surface energy of epoxy and urethane sized TCF is enhanced by 78% and 96%, respectively compared to unsized TCF. The storage modulus showed improvement for urethane (23%) and epoxy (21%) sized than unsized TCF-TSU composites. The flexural, interlaminar shear strength (ILSS), and impact properties of urethane sized TCF increase by 24%, 50%, and 273%, respectively, than unsized TCF. The results demonstrate that the surface and thermal properties correlate with the mechanical properties of TCF-TSU composites and sizing enhances the wettability of the composites. Graphical Abstract: ga1 Highlights: The Carbon Fiber Technology Facility (CFTF) at Oak Ridge National Laboratory (ORNL) produced textile carbon fiber (TCF). The interfacial adhesion of unsized, epoxy and urethane sized TCF to thermoset urethane (TSU) resin was investigated. The sizing interaction showed chemical interaction through hydrogen bonding between TCF-TSU composites. The surface, thermal and mechanical characterization showed improved wettability with urethane sizing.